Optimalisasi E-Commerce Dalam Meningkatkan Penjualan UMKM Prabu Jaya Almunium - Retno Cahyaningati; Ninik Lukiana; Kasno Kasno; M Wimbo Wiyono; Muhammad Rijalus Sholihin; Deni Juliasari (Indonesia Berdaya, 2021)
The Covid-19 pandemic has dealt a severe blow to Indonesian MSMEs. The existence of Covid 19 has paralyzed the world economy, including many MSME businesses that have gone out of business. However, there are some MSMEs who benefit. Community Service Activities at MSME Prabu Jaya Almunium try to overcome some of the problems faced due to the impact of the covid 19 pandemic, this requires MSMEs to step more creatively and innovatively so that the sustainability of their business remains stable. Efforts to uncover sales are carried out by increasing the optimization of e-commerce, and financial management assistance so that financial stability is always maintained. The existence of this community service activity has proven to be able to increase sales at Prabu Jaya Aluminum SMEs, and can understand how to do good financial management, they can compile financial reports and apply accounting records on a regular basis, so that company performance can also be measured properly.Pandemi Covid – 19 telah memberikan pukulan telak terhadap UMKM Indonesia. Adanya Covid 19 telah melumpuhkan perekonomian dunia termasuk bisnis UMKM banyak yang gulung tikar. Namun ada beberapa UMKM yang diuntungkan. Kegiatan Pengabdian Masyarakat pada UMKM Prabu Jaya Almunium mencoba untuk mengatasi beberapa permasalahan yang dihadapi karena pandemi covid 19, hal ini menuntut UMKM untuk melangkah lebih kreatif dan inovatif agar berusaha tetap stabil. Upaya peningkapan penjualan yang dilakukan adalah dengan meningkatkan optimalisasi e-commerce,dan pendampingan pengelolaan keuangan agar kestabilan keuangan selalu terjaga. Adanya Kegiatan Pengabdian masyarakat ini terbukti dapat meningkatkan penjualan pada UMKM Almunium Prabu Jaya, serta dapat memahami bagaimana cara melakukan pengelolaan keuangan yang baik, mereka dapat menyusun laporan keuangan dan menerapkan akuntansi secara berkala, sehingga kinerja perusahaan juga dapat diukur dengan baik.